Interrogantes sobre genealogía y dinámicas de la ciudadanía - Pompejano, Daniele (2006)
The main hypotesis of this article relys on the Colonial social relationship and the neoclassicists philosophy as the roots of Latin America authoritarian rule. From the concept of “natural” human being, patronizing and clientelism drove to an asymmetric relationship between authority and individuals within a corporative society. Although the Borbonism and liberalism had been strong dynamic forces, they were unsuccessful for changing such scheme and only a secularization process could timidly be carried on. For consequence, the Latin America politic modernization went on an authoritarian way, turning to populism, whereas individual became subaltern of the State; so, citizenship become indefinitely postponed.